LISENSI PENGUMUMAN LAGU ATAU MUSIK DALAM PERSFEKTIF HUKUM PERDATA - Bernard Nainggolan (to-ra, 2016)
The right to announce song or music, Which called in international with the performing rights or the public performance right is a part from economic right the creator of song or music. When its parsed, the right to announce consist of broadcast right, demonstrating right, announcing or utters right, as well to communicate song or musci right to the public. If so in announced right song or music bring in economic benefits to the creator of song or music, therefore needs to be given license to the user citizen song or music. However, in giving those license, might be effective, needs to be presence any institution License of principle and Collector Royalty in togetherness, that called as Collective Management Organization (CMO). Practically that has been held this periode in Indonesia, the granting of announcement license song or music is not doing by the creator or the holder copy right, but the State Public Institution (LMK) in blanket license form. So, State Public Institution with handing the representative letter from the creator of song or music giving license to useful song or music, to collect the Royalty, and then to distributing the Royalty to the people who has authority. At the view of private law, the announcement license of song or music is like an agreement what ought to have maded in written form. Its can not consist of rules which is able to harmful the state economic dan can not contain s of many things that contrast with the rule of laws. In other hand, that can be binding to the third side, therefore these license agreement of copy right must be noted in the Ministry of Law and Human Rights Indonesian Republic of Indonesia, the Directorate General of Intelctual Riches. Thereby the announcement of license song or music based on to the Private law include Formal Agreement type and from the management is an Annonymous Agreement (Onbenoemnde contract) or General Agreement type. Keywords: lisensi; pengumuman lagu atau musik